Revisiting Haraway's Cyborg Myth: A Case Study of Female Cyborg Characters in Marvel Comics - Zhou, Ziqing (Transactions on Social Science, Education and Humanities Research, 2024)
This paper revisits Donna Haraway's Cyborg Myth through a case study of female cyborg characters in Marvel Comics. Haraway's Cyborg Manifesto presents the cyborg as a hybrid entity that challenges traditional boundaries of gender, identity, and technology, offering a framework for feminist theory and posthumanism. By analyzing characters such as Misty Knight, Jocasta, and Lady Deathstrike, this study explores how these figures embody or challenge the cyborg myth and its feminist implications. The analysis reveals the nuanced portrayals of female cyborgs in Marvel, highlighting themes of empowerment, identity, and technological integration. This study contributes to the understanding of cyborg representation in popular culture and its relevance to contemporary feminist discourse.